Analytical narrative on subnational democracies in Colombia : clientelism, government and public policy in the Pacific region /: clientelism, government and public policy in the Pacific region. ([2019]) - Cendales, Andrés; Pinto, Angela; Mora, Jhon James; Guerrero, Hugo
No abstract available